1991
DOI: 10.1159/000125711
|View full text |Cite
|
Sign up to set email alerts
|

Role of Central Dopaminergic Pathways in the Neural Control of Growth Hormone Secretion in Normal Men: Studies with Metoclopramide

Abstract: The aim of this study was to gain further insight into the role that central dopaminergic pathways play in GH neuroregulation in man. Our experimental hypothesis was based on the possibility that most of the controversies on DA role could be due to the fact that the hypothalamic somatotroph rhythm (HSR) was not taken into account when interpreting the GH responses after pharmacological manipulations on dopaminergic pathways. In 10 normal subjects we monitored the effect of central dopaminergic blockade, achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
9
1
1
Order By: Relevance
“…Dopamine releases GHRH and SRIF from the hypothalamus, and the final GH response to dopamine is dependent on the endogenous DA tone (15). Induction of dopaminergic blockade in 10 normal human subjects increased GHRH-induced GH secretion and caused a loss of the relationship between pre-GHRH plasma GH values and GHRH-elicited GH peaks, suggesting that central DA may stimulate SRIF secretion (28). DA-induced SRIF release has also been observed in the rat (29).…”
Section: Discussionmentioning
confidence: 94%
“…Dopamine releases GHRH and SRIF from the hypothalamus, and the final GH response to dopamine is dependent on the endogenous DA tone (15). Induction of dopaminergic blockade in 10 normal human subjects increased GHRH-induced GH secretion and caused a loss of the relationship between pre-GHRH plasma GH values and GHRH-elicited GH peaks, suggesting that central DA may stimulate SRIF secretion (28). DA-induced SRIF release has also been observed in the rat (29).…”
Section: Discussionmentioning
confidence: 94%
“…GH secretion in the pituitary is mainly regulated by GHRH and somatostatin, both of which are derived from the neurosecretory nuclei of the hypothalamus and are controlled by dopamine (Tannenbaum and Ling 1984;Arce et al 1991;Müller et al 1999). García-Tornadú et al (2006) showed that a loss of dopamine signaling via the hypothalamic D2R caused the reduced release of GHRH from hypophysiotropic neurons in D2R knockout mice, suggesting that hypothalamic D2R plays an important role in GHRH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Arce et al (1991) showed that blockade of the central dopaminergic pathway by metoclopramide in 10 normal human subjects increased GHRH-induced GH secretion, possibly by inhibiting the hypothalamic release of somatostatin. The modest increase in serum GH by metoclopramide in the present case may be caused by the blockade of the central dopaminergic pathway as well as its antagonistic action on D2R in the pitu- itary adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine also inhibits GH secretion from cultured pituitary cells, i.e. at the pituitary level (37,38). In contrast, the systemic administration of dopamine results in GH increment (27), probably due to the activation of hypothalamic hormones stimulating GH release.…”
Section: Journal Of Endocrinology (1999) 140mentioning
confidence: 99%